Analysis of the Impact of Population Growth, Inflation Rate, and Foreign Investment on Economic Growth in Eight Developing Countries from an Islamic Economic Perspective - Rokhimah; Ariyani, Fitrah; Indarningsih, Nur Aisyah; Karfin; Hasrun, Andi (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This study aims to examine the impact of population growth, inflation rate, and foreign direct investment on economic growth in eight developing countries from the perspective of Islamic economics. Secondary data were sourced from the World Bank for the period 2016 to 2021. Panel data regression analysis was employed to test the established hypotheses, considering these independent variables. The results indicate that population growth, inflation rate, and foreign direct investment do not have a significant effect on economic growth in these countries during the study period. These findings are interpreted within the framework of Islamic economics, which emphasizes principles of economic justice, wealth distribution, and resource management in accordance with Shariah law. This research provides deep insights into how conventional economic factors interact with Islamic economic principles and their implications for economic policy in developing countries